дарсДАН ТАШҚАРИ МАШҒУЛОТЛАРДА талабаЛАРнинг ИЖТИМОИЙ ФАОЛ ФУҚАРОЛИК КОМПЕТЕНТЛИГИНИ ШАКЛЛАНТИРИШ БЎЛАЖАК КАСБИЙ МУВАФФАҚИЯТ ОМИЛИ СИФАТИДА - Жалиев, Т. (SCIENCE and SOCIETY, 2021)
The article is devoted to the analysis of the influence of socially active civic competence formed in students on the success of the future professional activity of graduates. Various approaches to understanding professional success are analyzed, socially active civic competence is considered as the main factor. Based on the study of the influence of extracurricular activities on the formation of such components of socially active civic competence of students as the consciousness of their values and motivation for success, the conclusion is made about the influence of extracurricular activities on the formation of socially active civic competence.
Keywords: socially active civic competence; indicators and factors of success; knowledge; skills; qualification; success of professional activity; value basis of activity; strategies for achieving success